2020
DOI: 10.3389/fcvm.2020.00065
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein and Its Precursor Protein Apolipoprotein A1 as Potential Therapeutics to Prevent Anthracycline Associated Cardiotoxicity

Abstract: Cardiovascular disease and cancer are the leading causes of death in developed societies. Despite their effectiveness, many cancer therapies exhibit deleterious cardiovascular side effects such as cardiotoxicity and heart failure. The cardiotoxic effects of anthracyclines such as doxorubicin are the most well-characterized of cardiotoxic anti-cancer therapies. While other anti-neoplastic drugs also induce cardiotoxicity, often leading to heart failure, they are beyond the scope of this review. This review firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 174 publications
(261 reference statements)
0
7
0
Order By: Relevance
“…In support of this concept, the role of SR-B1 in drug delivery is consistent with the flow cytometry findings revealed in this communication, showing the inhibition of ChO* uptake when SR-B1 is blocked (Figure ). Accordingly, the drug payload delivery is achieved without endocytosis of the NP itself, a unique and essential feature of this system, compared to most other nanodelivery approaches. , Overexpression of SR-B1 by malignant tumors is an important feature, especially in aggressive cancers. , Our laboratory and several others have reported tumor selective delivery by rHDL nanoparticles via this receptor. , In the present study, we show potentially tumor-selective delivery of the therapeutic payload by the MYR-5A/AD198 NCs, indicating that this formulation is an excellent candidate for personalized therapy for Ewing sarcoma patients and those with other malignancies without affecting off-target (especially cardiac) damage.…”
Section: Resultsmentioning
confidence: 53%
“…In support of this concept, the role of SR-B1 in drug delivery is consistent with the flow cytometry findings revealed in this communication, showing the inhibition of ChO* uptake when SR-B1 is blocked (Figure ). Accordingly, the drug payload delivery is achieved without endocytosis of the NP itself, a unique and essential feature of this system, compared to most other nanodelivery approaches. , Overexpression of SR-B1 by malignant tumors is an important feature, especially in aggressive cancers. , Our laboratory and several others have reported tumor selective delivery by rHDL nanoparticles via this receptor. , In the present study, we show potentially tumor-selective delivery of the therapeutic payload by the MYR-5A/AD198 NCs, indicating that this formulation is an excellent candidate for personalized therapy for Ewing sarcoma patients and those with other malignancies without affecting off-target (especially cardiac) damage.…”
Section: Resultsmentioning
confidence: 53%
“…Nevertheless, it is crucial to note that HDL-C levels may not accurately reflect the functional properties of HDL. ApoA1, the most abundant protein in HDL, is associated with several beneficial effects of HDL 15 25. The function and abundance of ApoA1 are reported to play a dominant role in HDL quality 26.…”
Section: Discussionmentioning
confidence: 99%
“…ApoA1, the most abundant protein in HDL, is associated with several beneficial effects of HDL. 15 25 The function and abundance of ApoA1 are reported to play a dominant role in HDL quality. 26 In the context of AIC, several studies have indicated that HDL can protect against anthracycline-induced cardiomyocyte apoptosis and atrophy in isolated cardiomyocytes 27 28 and animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apo-A1, along with HDL, is well-known for its vasoprotective effects, being involved in the “reverse cholesterol transport” from the periphery to the liver and in arterial plaque inhibition in part via antiinflammatory effects ( 50 ). Apo-A1 is the major protein component of HDL and has been suggested to protect the cardiovascular system against AC toxicity via cytoprotective effects and cardiac “sparing” in delivery of AC ( 51 ). Whether Apo-A1 might be the driving mechanism of the effect observed herein needs to be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%